Nanopore detection of copper ions using a polyhistidine probe - Wang, Guihua; Wang, Liang; Han, Yujing; Zhou, Shuo; Guan, Xiyun (Biosensors & bioelectronics, 2014)
We report a stochastic nanopore sensing method for the detection of Cu(2+) ions. By employing a polyhistidine molecule as a chelating agent, and based on the different signatures of the events produced by the translocation of the chelating agent through an α-hemolysin pore in the absence and presence of target analytes, trace amounts of copper ions could be detected with a detection limit of 40 nM. Importantly, although Co(2+), Ni(2+), and Zn(2+) also interacts with the polyhistidine molecule, since the event residence times and/or blockage amplitudes for these metal chelates are significantly different from those of copper chelates, these metal ions do not interfere with Cu(2+) detection. This chelating reaction approach should find useful application in the development of nanopore sensors for other metal ions.